Influence of early hemodialysis on the septic acute kidney injury outcome* - Queiroz, Cléria Alves de; Bacci, Marcelo Rodrigues (Revista da Escola de Enfermagem da USP, 2022)
Objective: to analyze the influence of early hemodialysis on the outcome of acute septic kidney injury. Method: this is an observational, analytical, prospective study with patients diagnosed with acute septic kidney injury on hemodialysis. A questionnaire for data collection was used as an instrument. We used the Shapiro-Wilk, nonparametric Kruskal-Wallis, Mann-Whitney U, Student t and chi-square tests for analysis. Results: of the 40 patients analyzed, 60% were male, with a mean age of 55 (±16.8) years, and length of hospital stay of 43 (±26.2) days. When separating patients undergoing early and late hemodialysis into two groups, an increase in serum creatinine (p = 0.001) was observed in those who underwent late hemodialysis, however, creatinine ≥ 4mg/dl is one of the characteristics of this group. In both groups, there was a high mortality: 62.5% (10) in the early hemodialysis group and 41.7% (10) in the late hemodialysis group, with vasopressor use (p = 0.001) being the main risk factor. Conclusion: early onset of hemodialysis in acute septic kidney injury based on KDIGO definitions did not influence the outcome. However, vasopressor use associated with hemodialysis in septic patients was a predictor of death.